Actividad repelente de aceites esenciales contra las picaduras de Lutzomyia migonei (Diptera: Psychodidae) - Nieves, Elsa (2010)
Natural repellents from plant extracts have demonstrated good efficacy against bites of some insect species. The present study evaluated the repellent effect of essential oils extracted from 8 plants species against bites of Lutzomyia migonei, the Leishmania vector. The essential oils were extracted by steam destilla-tion in Clevenger chamber, from the following plants: Hyptis suaveolens, Pimenta racemosa, Piper marginatum, Monticalia imbricatifolia, Pseudognaphalium caeruleocanum, Espeletia shultzii, Plecthranthus amboinicus and Cinnamomun zeylanicum. Repellency tests were performed under laboratory conditions by the human hand method in cage assays, using female colonies of L. migonei. The more effective oils were tested at variable concentrations on different volunteers. The protection percentage and time were calculated. The results showed what oils of P. caeruleocanum and C. zeylanicum were the most effective. Although P. amboinicus oil also had repellent effect showed an irritant effect. The oils P. marginatum, H. suaveolens and P. racemosa showed no repellent effect, while the rest of oil extracts showed significant repellency in variable degrees. P. caeruleocanumand C. zeylanicum oils provided the 95% protection against bites of L. migonei for 3h. The P. caeruleocanum oil showed the greatest protection time, with a mean over 4h and 3h at concentrations of 50% and 10% respectively. The results suggest that the P. caeruleocanum oil could represent a potential natural repellent against Leishmaniavectors.